Meningkatkan Konsentrasi Belajar melalui Bimbingan Kelompok dengan Teknik Group Exercise - Sriana, Sriana; Darmawani, Evia; Ramadhani, Erfan (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
This research is motivated by the existence of students' problems related to low concentration in learning, such as the ability to focus, oral speech ability and psychomotor speech ability. This study aims to increase the concentration of student learning after the implementation of group guidance services with group exercise techniques. This study uses the Guidance Counseling Action research method (PT-BK) with two cycles. The population and sample in this study were 10 students of class XII of SMK Shailendra Palembang. The data collection techniques used include: (1) Observation, (2) Documentation. The data analysis technique used in this research is descriptive quantitative data analysis with percentages. The results of this counseling guidance action research (PT-BK) indicate that, through group guidance with group exercise techniques, it can increase learning concentration. The increase is known from the increase in indicators in each cycle, in the first cycle 50% focus ability, quite good 40% oral speech ability, quite good and 50% psychomotor speech ability, quite good while in the second cycle there is a significant increase, namely 80% focus ability, both 70% good oral speech ability and 90% psychomotor speech ability, good.